Research on the Depletion and Recovery Characteristics of Fault-Karst Reservoirs - Bochao Tang; Chunying Geng; Mina Huang; Haitao Lu; Ke Ren (Geofluids)
A fractured-vuggy carbonate reservoir is a special reservoir formed by long-term physical, chemical, and geological processes. Its reserves are large in scale and widely distributed, showing the characteristics of free flow-seepage coupling. Conventional simulation is usually simplified by equivalent permeability, which cannot reflect the actual development characteristics. Given this, the flow in caves and fractures is treated with free flow, using the Navier–Stokes equation. The seepage simulation is used for other areas, and the Darcy formula is used. Finally, the simulation results are obtained by coupling, and the influence of oil production speed, fracture-cavity size, fracture-cavity location, dynamic viscosity, permeability, and other factors on bottom pressure is analyzed to effectively guide the field development. The results show that the production pressure of fractured-vuggy reservoirs diffuses from the central fractured-vuggy area to the surrounding matrix, and the pressure increases from the fractured-vuggy area to the surrounding matrix. The flow velocity in the seepage area is relatively stable and flows gently into the middle fracture cavity from all directions. There will be eddy current in the free-flow area. Different factors have different effects on the development. The oil production speed and oil dynamic viscosity are positively correlated with it, while the formation permeability is negatively correlated with it. The size and location distribution of fracture cavity will also have a certain impact. Simulation in advance can effectively avoid some reservoir development problems.